2023
DOI: 10.1002/ca.24098
|View full text |Cite
|
Sign up to set email alerts
|

A new dimension in medical education: Virtual reality in anatomy during COVID‐19 pandemic

Ilia Miltykh,
Edgar S. Kafarov,
Serghei Covantsev
et al.

Abstract: Virtual reality technology has been increasingly used in the field of anatomy education, particularly in response to the COVID‐19 pandemic. Virtual reality in anatomy (VRA) allows the creation of immersive, three‐dimensional environments or experiences that can interact in a seemingly real or physical way. A comprehensive search of electronic databases was conducted to identify relevant studies. The search included studies published between 2020 and June 2023. The use of VRA education has been shown to be effe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 79 publications
(90 reference statements)
0
2
0
Order By: Relevance
“…As such, complementary tools, including interactive technologies, are being incorporated into the teaching and learning of Human Anatomy subjects 83,84 . XR‐based technologies, such as iVR and AR, have drawn more attention in recent years, especially motivated during the COVID‐19 pandemic 85 . Between 2019 and 2022 several scoping and systematic reviews, without meta‐analyses, were published and collectively suggested that XR‐based interventions are effective for learning human anatomy 1,2,4,8,27,28 .…”
Section: Discussionmentioning
confidence: 99%
“…As such, complementary tools, including interactive technologies, are being incorporated into the teaching and learning of Human Anatomy subjects 83,84 . XR‐based technologies, such as iVR and AR, have drawn more attention in recent years, especially motivated during the COVID‐19 pandemic 85 . Between 2019 and 2022 several scoping and systematic reviews, without meta‐analyses, were published and collectively suggested that XR‐based interventions are effective for learning human anatomy 1,2,4,8,27,28 .…”
Section: Discussionmentioning
confidence: 99%
“…5 Virtual Reality (VR) is also gaining popularity in educating the medical students and has been demonstrated to be beneficial in enhancing students' comprehension and memory as well as in the development of transferable skills like surgical methods. 6 The medical schools in South Asian countries need to reiterate the development/enhancement of clinical reasoning skills of both medical undergraduate and postgraduate learners. To achieve this objective, medical colleges must regularly organize training for clinical medical educators to facilitate students' learning in reasoning skills, and for assessing their skills, and provide feedback to the learners.…”
Section: Editorialmentioning
confidence: 99%